Cellulose-dependent expression and antibacterial characteristics of surfactin from Bacillus subtilis HH2 isolated from the giant panda - Zhou, Ziyao (PLoS One, 2018)
Surfactin secreted by Bacillus subtilis can confer strong, diverse antipathogenic effects, thereby benefitting the host. Carbon source is an important factor for surfactin production. However, the mechanism that bacteria utilize cellulose, the most abundant substance in the intestines of herbivores, to produce surfactin remains unclear. Here, we used B. subtilis HH2, isolated from the feces of a giant panda, as a model to determine changes in surfactin expression in the presence of different concentrations of cellulose by quantitative polymerase chain reaction and high-performance liquid chromatography. We further investigated the antimicrobial effects of surfactin against three common intestinal pathogens (Escherichia coli, Staphylococcus aureus, and Salmonella enterica) and its resistance to high temperature (60–121°C), pH (1–12), trypsin (100–300 μg/mL, pH 8), and pepsin (100–300 μg/mL, pH 2). The results showed that the surfactin expressed lowest in bacteria cultured in the presence of 1% glucose medium as the carbon source, whereas increased in an appropriate cellulose concentration (0.67% glucose and 0.33% cellulose). The surfactin could inhibit E. coli and Staphylococcus aureus, but did not affect efficiently for Salmonella enterica. The antibacterial ability of surfactin did not differ according to temperature (60–100°C), pH (2–11), trypsin (100–300 μg/mL), and pepsin (100–300 μg/mL; P > 0.05), but decreased significantly at extreme environments (121°C, pH 1 or 12; P < 0.05) compared with that in the control group (37°C, pH = 7, without any protease). In conclusion, our findings indicated that B. subtilis HH2 could increase surfactin expression in an appropriate cellulose environment and thus provide benefits to improve the intestinal health of herbivores.